Pengaruh Belajar Bahasa Arab Terhadap Kemudahan Menghafal Al-Qur'an Santri Ma'had Aly Pondok Qur'an Bandung - Renren Nurfauziah; Nanda Lestari; Rihhad Nazhmi Maulana; Shalma Herwinadira Afgani; Ahmad Fu’adin (Al-Mazaya: Jurnal Pendidikan Bahasa Arab, 2023)
The research that was carried out was motivated by the many factors that become challenges for someone to memorize the Qur’an at Santri Ma'had Ali Pondok Qur'an Bandung. The aim of this research is to analyze and prove the influence of learning Arabic and memorizing the Qur’an at the Ma'had Aly Pondok Qur'an Bandung. This research uses a descriptive quantitative method, where data collection is carried out by distributing questionnaires, then processing it into diagrams and presenting the data results descriptively. The resulting research shows that Arabic has an influence on memorizing the Qur’an, namely making it easier for students to remember the verses of the Qur’an by understanding their meaning and significance. Arabic helps to understand the verses of the Qur’an, because the Qur’an itself uses Arabic. The majority of students who can speak Arabic find it helpful when memorizing the Qur’an.